The Efficacy and Safety of Phase I Cardiac Rehabilitation in Patients Hospitalized in Cardiac Intensive Care Unit With Acute Decompensated Heart Failure: A Study Protocol for a Randomized, Controlled, Clinical Trial - Wu, Linjing; Li, Jiahua; Chen, Linjian; Xue, Mengmeng; Zheng, Yamin; Meng, Fanqi; Jiang, Hongfei; Shi, Zaixing; Zhang, Peng; Dai, Cuilian (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac rehabilitation (CR) improves outcomes in patients with heart failure. However, data on CR efficacy in patients with acute decompensated heart failure is limited. This study is designed to assess the efficacy and safety of CR in patients hospitalized in cardiac intensive care unit (CICU) with acute decompensated heart failure (ADHF). Methods This is a single-center, randomized controlled, single-blind clinical trial. A total of 120 participants hospitalized in CICU with ADHF will be randomly allocated in the ratio of 1:1 to two groups: CR group and control group. Participants will receive tailored and progressive CR intervention or attention control. The CR intervention include personalized breathing training, small muscle group resistance training, and aerobic endurance training based on the physical fitness assessment results. The subjects will receive the CR training for 5 days and will be followed up for 6 months. The primary endpoints are the score of the short physical performance battery (SPPB) and 6-month all-cause rehospitalization. The secondary endpoints include cardio-pulmonary function, activities of daily living (ADL), in-hospital mortality rate and 6-month all-cause mortality rate. Discussion This randomized, controlled, clinical trial will assess whether CR improves physical function and reduces rehospitalization in patients hospitalized in CICU with ADHF. The results will provide further research-based evidence for the clinical application of CR in patients with ADHF. Trial Registration Chinese Clinical Trial Registry ChiCTR2100050151. Registered on 19 August 2021.